2020
DOI: 10.2320/matertrans.mt-m2020200
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Dy-Alloying Behaviors of Ni-Based Alloys in Molten LiF–CaF<sub>2</sub>–DyF<sub>3</sub>: Effects of Constituent Elements

Abstract: The electrochemical Dy-alloying behaviors of NiCr and NiMo alloys were compared with those of NiCrMo alloy and pure Ni in a molten LiFCaF 2 DyF 3 (0.30 mol%) system at 1123 K. The effects of chromium and molybdenum as constituent elements of the Ni-based alloys were investigated. Cyclic voltammetry and open-circuit potentiometry indicated the formations of DyNi alloys for all the Ni-based electrodes, as well as for the pure Ni electrode. XRD analysis confirmed the formation of DyNi 2 and DyNi 3 phases for all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…During electrolysis, RE ions were oxidized and dissolved in the anode chamber, and specific RE element alloys were formed, which diffused through the IG diaphragm; finally, the RE metal was recovered at the cathode. Our previous studies confirmed that RE-Ni alloys (RE = Pr, Nd, Dy) are selectively formed via electrolysis by utilizing Ni-based substrates in the following molten electrolytes: LiCl-KCl-RECl 3 at 723 K, [12][13][14][15][16] NaCl-KCl-RECl 3 at 973 K, [17][18][19][20] and LiF-CaF 2 -REF 3 at 1123 K. 19,[21][22][23][24][25] In addition, this process exhibits a high RE separation ability over a specific potential range. However, the brittle nature of RE-Ni alloys results in durability issues in the alloy diaphragms.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…During electrolysis, RE ions were oxidized and dissolved in the anode chamber, and specific RE element alloys were formed, which diffused through the IG diaphragm; finally, the RE metal was recovered at the cathode. Our previous studies confirmed that RE-Ni alloys (RE = Pr, Nd, Dy) are selectively formed via electrolysis by utilizing Ni-based substrates in the following molten electrolytes: LiCl-KCl-RECl 3 at 723 K, [12][13][14][15][16] NaCl-KCl-RECl 3 at 973 K, [17][18][19][20] and LiF-CaF 2 -REF 3 at 1123 K. 19,[21][22][23][24][25] In addition, this process exhibits a high RE separation ability over a specific potential range. However, the brittle nature of RE-Ni alloys results in durability issues in the alloy diaphragms.…”
supporting
confidence: 63%
“…However, the brittle nature of RE-Ni alloys results in durability issues in the alloy diaphragms. 24,25 In our previous studies, solid RE-IG alloys have been mainly used as diaphragms (Fig. 1a); however, the liquid alloys should exhibit increased RE diffusivity rate than their solid counterparts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is necessary to develop an inexpensive and effective recovery/separation process of Dy from scraps of the Dy-added Nd-Fe-B magnet. From this background, we have been investigating a new recovery process of Dy and Nd from the magnet scraps using molten salt electrolysis and alloy diaphragms (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The key step in this process is the alloying and de-alloying of rare earth (RE) elements on both sides of the diaphragm in order to effectively separate them in the molten salt.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we reported the use of a Ni-Cr-Mo alloy (Hastelloy C-276) electrode as a durable diaphragm material. [28][29][30] In the above-mentioned studies, we used solid alloys of RE elements with Ni or Ni-based alloys, as candidate materials for the diaphragm; however, the diffusion of RE elements is expected to be much faster in liquid alloys than in solids. 31 Therefore, we focused on liquid Nd-Fe alloys as candidates for liquid alloy diaphragms and have already reported the results of our investigation of the electrochemical Nd alloying behavior of Fe electrodes in molten LiF-CaF 2 -NdF 3 at 1123 K. 32 In the previous study, we found that liquid Nd-Fe alloys were formed by potentiostatic electrolysis at 0.10 V vs Li + /Li.…”
mentioning
confidence: 99%